2016
DOI: 10.1038/srep38996
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mung bean hydration using the ultrasound technology: description of mechanisms and impact on its germination and main components

Abstract: The ultrasound technology was successfully used to improve the mass transfer processes on food. However, the study of this technology on the grain hydration and on its main components properties was still not appropriately described. This work studied the application of the ultrasound technology on the hydration process of mung beans (Vigna radiata). This grain showed sigmoidal hydration behavior with a specific water entrance pathway. The ultrasound reduced ~25% of the hydration process time. In addition, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 55 publications
(86 reference statements)
5
67
0
4
Order By: Relevance
“…Nevertheless, the acoustic cavitation during ultrasound treatment increases the porosity of the seeds facilitating oxygen availability and water uptake, which are the basic requirements for seeds to begin the first step of germination (Liu et al, ). Similar outcome is noticed by the Miano et al () who stated that there is ~25% reduction in the hydration process time by enhancing the seed germination. Further, many researchers have stated mechanisms for the biological effect of the US on sprouting.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the acoustic cavitation during ultrasound treatment increases the porosity of the seeds facilitating oxygen availability and water uptake, which are the basic requirements for seeds to begin the first step of germination (Liu et al, ). Similar outcome is noticed by the Miano et al () who stated that there is ~25% reduction in the hydration process time by enhancing the seed germination. Further, many researchers have stated mechanisms for the biological effect of the US on sprouting.…”
Section: Resultssupporting
confidence: 87%
“…Various treatments such as physical scarification, acid treatment, effect of nitrogenous compounds, and seaweed extracts were studied by several researchers to enhance the sprouting rate of the legumes. Miano, da Costa Pereira, Castanha, da Matta Júnior, and Augusto () noticed the effect of ultra‐sonication (US) treatment (25 kHz) on the hydration rate of the green gram. The study demonstrated that the hydration rate of green gram improved by reducing the hydration time by 25% (increasing the water absorption rate ~44%).…”
Section: Introductionmentioning
confidence: 99%
“…This technology reduces the hydration process time almost 40% at 25°C from 480 to 300 min. This value is similar to the work of Miano, Ibarz, and Augusto () that reduced 35% of the processing time (25°C) for corn kernels ( Zea mays) ; Patero and Augusto () that reduced 40% of the processing time (25°C) for sorghum kernels ( Sorghum sp ); Ghafoor et al () that reduced 45% of the processing time (16°C) for navy beans ( Phaseolus vulgaris ); Miano, Pereira, Castanha, Júnior, and Augusto () that reduced 25% of the processing time (25°C) for mung beans ( Vigna radiata ); and to the work of Miano et al () that reduced 30% of processing time (30°C) for white kidney beans ( P. vulgaris) . It should be mentioned that this result depends on the applied volumetric power of ultrasound, since as the power is increased; the hydration is accelerated (Yildirim et al, ).…”
Section: Resultssupporting
confidence: 86%
“…Consequently, ultrasound reduced the time to reach the same equilibrium moisture in approximately 3.3 hr (50%) when compared to the control. In fact, the improvement of hydration process by ultrasound has been also demonstrated, reducing the process time approximately 40% for chickpeas (Yildirim, Öner, & Bayram, ), approximately 40% for sorghum grains (Patero & Augusto, ), approximately 35% for corn kernels (Miano et al., ), approximately 25% for mung beans (Miano et al., ), approximately 30% for white kidney beans (Miano et al., ), and approximately 45% for carioca beans (Miano & Augusto, ). It should be mentioned that all these reported results were obtained using an ultrasonic water bath at room temperature, but at different volumetric powers.…”
Section: Resultsmentioning
confidence: 99%
“…This causes a quick change of the seed coat permeability, reducing the lag phase time. All the published works that used ultrasound for hydrating grains with sigmoidal behavior have demonstrated the reduction of lag phase time (Miano & Augusto, ; Miano et al., , ).…”
Section: Resultsmentioning
confidence: 99%